Design and Preliminary Testing of the Caregiver-Centered Communication Questionnaire (CCCQ). Issue 3 (July 2020) - Demiris, George; Ganz, Freda DeKeyser; Han, Claire J.; Pike, Kenneth; Oliver, Debra Parker; Washington, Karla
The study objective was to develop and test a new survey instrument that measures caregiver-centered communication. We developed a questionnaire inspired by the National Cancer Institute framework on patient-centered communication, focusing on family caregiver communication for this tool. The questionnaire includes 5 subscales: exchange of information, relationship with team, emotions, managing care, and decision-making. The initial questionnaire was reviewed by domain experts for face validity and edited further to include 30 items. We administered the modified questionnaire to 115 family caregivers of patients with serious illness in various settings. Cronbach α for the entire scale was 0.97 and ranged from 0.82 to 0.93 for the 5 subscales. Participants found that the survey addressed important concepts and that items were in most cases easy to understand. This instrument provides a structured way to assess caregiver-centered communication, addressing a pressing need for tools that measure the extent to which communication is responsive to the needs and preferences of family caregivers. Further testing and refinement are needed to improve the ease of use and examine the reliability and validity of this measure.